2021
DOI: 10.3390/plants10030544
|View full text |Cite
|
Sign up to set email alerts
|

Water Use Efficiency and Stress Tolerance of the Potential Energy Crop Miscanthus lutarioriparius Grown on the Loess Plateau of China

Abstract: As a potential energy crop with high biomass yield, Miscanthus lutarioriparius (M. lutarioriparius), endemic to the Long River Range in central China, needs to be investigated for its acclimation to stressful climatic and soil conditions often found on the marginal land. In this study, traits related to acclimation and yield, including survival rates, plant height (PH), stem diameter (SD), tiller number (TN), water use efficiency (WUE), and photosynthetic rates (A), were examined for 41 M. lutarioriparius popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 55 publications
0
4
0
1
Order By: Relevance
“…Although the high photosynthetic rate is due to the high stomatal conductance, it can increase the expense of additional transpiration ( Dohleman et al., 2009 ). It was acknowledged that small stomatal conductance was more conducive to coping with the poor external environment ( Leakey, 2009 ; Zhao et al., 2021 ). The plant could have suffered severe drought stress when the stomatal conductance decreased ( Ings et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the high photosynthetic rate is due to the high stomatal conductance, it can increase the expense of additional transpiration ( Dohleman et al., 2009 ). It was acknowledged that small stomatal conductance was more conducive to coping with the poor external environment ( Leakey, 2009 ; Zhao et al., 2021 ). The plant could have suffered severe drought stress when the stomatal conductance decreased ( Ings et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The female parent of M. sacchariflorus was from a population native to the Loess Plateau, adapted to the cold and drought environment but producing relatively low biomass ( Yan et al., 2012 ). M. lutarioriparius , an endemic species in Central China with the highest biomass production, has been shown to have high water use efficiency and high yield in certain locations of the Loess Plateau where it was able to overwinter ( Yan et al., 2015 ; Zhao et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…M. sacchariflorus has a high level of genetic diversity and adaptation. Literature has also suggested that the two species had been transplanted on the Loess Plateau of northwestern China, which demonstrated that they had great potential to serve as suitable progenitors in perennial energy crop breeding programs [6][7][8]. Compared to M. sacchariflorus, M. lutarioriparius has lower heritability of traits such as cold and drought tolerance, and lower establishment rates in the Loess Plateau.…”
Section: Introductionmentioning
confidence: 99%
“…A través de su evolución las plantas han desarrollado mecanismos de defensa a nivel morfológico, fisiológico, bioquímico, celular y molecular, para poder superar las condiciones de déficit hídrico y el estrés por sequía (Lesk et al, 2016;Zhao et al, 2021). La resistencia a la sequía de las plantas se puede clasificar en cuatro tipos básicos: prevención de la sequía, tolerancia a la sequía, escape a la sequía y recuperación de la sequía (Fang y Xiong, 2015).…”
Section: Introductionunclassified